Impact of stratospheric air and surface emissions on tropospheric nitrous oxide during ATom - Gonzalez, Yenny; Commane, Róisín; Manninen, Ethan; Daube, Bruce C.; Schiferl, Luke; McManus, J. Barry; McKain, Kathryn; Hintsa, Eric J.; Elkins, James W.; Montzka, Stephen A.; Sweeney, Colm; Moore, Fred; et al. (2021)
Nitrous oxide (N 2 O) is both a greenhouse gas in the troposphere and an ozone depleting substance in the stratosphere and is rapidly increasing in the atmosphere. The spatial distribution of N 2 O emissions and the sources leading to rising concentrations in the global atmosphere are highly uncertain. We measured the global distribution of tropospheric N 2 O mixing ratios during the airborne Atmospheric Tomography (ATom) mission. ATom measured mixing ratios of ~300 gas species and aerosol properties in 647 vertical profiles spanning the Pacific, Atlantic, Arctic, and much of the Southern Ocean basins, from nearly Pole to Pole, over four seasons (2016–2018). We measured N 2 O mixing ratios at 1 Hz using a Quantum Cascade Laser Spectrometer and a new spectral retrieval method to account for the pressure and temperature sensitivity of the instrument when deployed on aircraft. This retrieval strategy improved the precision of our N 2 O measurements by a factor of 3, enabling us to recover the precision to that of previous missions. Most of the variance of N 2 O mixing ratios in the troposphere is driven by the influence of N 2 O-depleted stratospheric air, especially at mid and high latitudes. We observe the downward propagation of lower N 2 O mixing ratios (compared to surface stations) that tracks the influence of stratosphere-troposphere exchange through the tropospheric column down to the surface, resulting in a seasonal minimum at the surface 2–3 months after the peak stratosphere-to-troposphere exchange in spring. The highest N 2 O mixing ratios occur close to the equator, extending through the boundary layer and free troposphere. We observed influences from a complex and diverse mixture of N 2 O sources, with emission source types identified using the rich suite of chemical species measured on ATom and with the geographical origin calculated using an atmospheric transport model. Although ATom flights were mostly over the oceans, the most prominent N 2 O enhancements were associated with anthropogenic emissions, including industry, oil and gas, urban and biomass burning, especially in the tropical Atlantic outflow from Africa. Enhanced N 2 O mixing ratios are mostly associated with pollution-related tracers arriving from the coastal area of Nigeria. Peaks of N 2 O are often well-correlated with indicators of photochemical processing, suggesting possible unexpected source processes. The difficulty of separating the mixture of different sources in the atmosphere contributes to uncertainties in the N 2 O global budget. The extensive data set from ATom will help improve the understanding of N 2 O emission processes and their representation in global models.